Classifying problematic gaming using a latent profile approach based on personality traits in Chinese young adolescent - Jingyue Hao; Zhenjiang Liao; Qiuping Huang; Xinxin Chen; Shuhong Lin; Yongyan Shi; Yifan Li; Yin Tang; Xuhao Wang; Hongxian Shen (BMC Psychiatry)
Abstract Background Internet gaming has gained widespread popularity in China, yet the classification of problematic gaming subtypes based on personality traits remains limited. This study aimed to employ latent profile analysis (LPA) to identify distinct groups of online gamers and compare key variables across these groups. Methods An online survey was conducted within 5593 internet gaming users, including a demographic questionnaire, queries on internet gaming usage, the Video Gaming Dependency Scale, and the Chinese Big Five Inventory-brief version. LPA was applied to identify distinct user groups, followed by an examination of associations between profile membership and auxiliary variables. Results LPA identified three gamer categories for problematic gaming: “high-risk” (64.78%), “medium-risk” (3.22%), and “low-risk” (32%). High-risk gamers allocated more time and financial resources to gaming for escapism and leisure purposes. The medium-risk group sought enjoyable experiences, exhibiting traits that were intermediate between the high- and low-risk groups. High-risk gamers demonstrated elevated levels of neuroticism, accompanied by lower scores in other Big Five personality traits. In contrast, medium-risk gamers scored low across all Big Five dimensions, while low-risk gamers achieved higher scores in all traits except neuroticism. Notably, the low-risk group reported forming the fewest new online friendships, despite sharing similar social motivations with the other groups. Conclusion Traits such as low neuroticism and high conscientiousness serve as protective factors against gaming addiction, while being unmarried or an only child provides additional safeguards. Conversely, increased time and financial investment in gaming activities are associated with a heightened risk of addiction. These findings are crucial for identifying high-risk gamers and informing the development of targeted interventions.